Pengaruh Terpaan Iklan Media Luar Ruang dan Frekuensi Diskusi Antar Tetangga Terhadap Perilaku Disiplin Protokol Kesehatan (Studi Deskriptif Kuantitatif Pada Masyarakat Kecamatan Pedurungan Kota Semarang) - Ayu Emilia Kurniawati; Adi Nugroho; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
One of the regions in Indonesia that recorded the highest positive cases of COVID-19 from January to March 2021 is Semarang City, especially in Pedurungan District. The government has made efforts to suppress the increase in COVID-19 cases by formulating health protocol behavioral policies such as washing hands, wearing masks, maintaining distance, staying away from crowds, and limiting mobility. Various forms of policy socialization have been carried out to provide knowledge to the public about the urgency of this disciplined behavior, such as by disseminating information through outdoor media advertisements and cooperation between neighbors in the form of discussions about COVID-19. However, the Covid-19 case is still not sloping due to the fact that there are still violations of health protocols carried out by the community. Therefore, this study was conducted with the aim of analyzing how the influence of exposure to outdoor media advertising and the frequency of discussions between neighbors on the disciplinary behavior of health protocols. This type of research is quantitative explanatory with sampling technique in the form of non-probability sampling technique. The number of samples in this study were 68 respondents with all gender criteria, domiciled in Pedurungan District, aged 20-54 years, had been exposed to outdoor media advertisements about covid-19 in the last 8 months (August 2020-March 2021), and have had discussions between neighbors regarding covid-19 in the last 8 months. The theory used is Elaboration Likelihood Theory and Theory of Reasoned Action. Meanwhile, data analysis was performed using a simple linear regression test. The results in this study indicate that there is no significant effect between exposure to outdoor media advertising on the disciplinary behavior of health protocols because the hypothesis significance value of 0.501 is greater than 0.05. Meanwhile, the frequency of discussions between neighbors can have a significant effect on the disciplinary behavior of health protocols with a significance value of 0.015 which is smaller than 0.05.